Challenges and Strategies to Improve Potato Competitiveness along with Potato Value Chain in Bangladesh - Hossain, M.F.; Rahman, Md. Shamimur (AIUB Journal of Business and Economics, 2016)
Potato (disambiguation), Solanum tuberosum, is a tuberous crop grown throughout the world. It is the world's fourth-largest food crop, following maize, wheat, and rice. Potato is the leading vegetable in Bangladesh. The potential to strategize the ways of enhancing its competitiveness in the value chain remains locked and unexploited due to a host of constraining factors along its value chain, which must be addressed. This paper identifies the underlying constraints and proposes strategic interventions to enhance Potato competitiveness along the value chain in Bangladesh. Secondary data has been obtained from Ministry of Agriculture, Bangladesh Agricultural Research Institute (BARI), Department of Agriculture Extension (DAE), Bangladesh Agriculture Development Corporation (BADC), Bangladesh Firm Seeds Trade Federation of Bureau and Bangladesh Bureau of Statistics. The data were analyzed using statistically. Underlying constraints such as production inefficiencies, market inaccessibility, and inadequate processing facilities and consumers’ exploitation through inflated pricing were identified to affect potato value chain performance. Strategic interventions like the adoption of tissue culture technology, rapid multiplication method, top shoot cutting, appropriate irrigation systems and business model aggregator were identified to enhance potato value chain competitiveness. Government was therefore recommended to partner with all stakeholders in order to enhance performance in potato value chain.